1928
DOI: 10.1524/zkri.1928.67.1.583
|View full text |Cite
|
Sign up to set email alerts
|

XLIII. Röntgenuntersuchungen über den Bau der C-Ketten in Kohlenwasserstoffen (CnH2n+2)

Abstract: In den letzten Jahren sind eine Reihe von aliphatischen Verbindungen und speziell Kohlenwasserstoffe mit 15-35 C-Atomen eingehend strukturanalytisch untersucht worden 1 ). Diese Stoffe sind nur sehr schwer oder gar nicht in größeren Einkristallen zu erhalten, wie das für eine vollständige Strukturbestimmung notwendig wäre. Es hat sich aber gezeigt, daß sie sich auf Glasplättchen als gerichtete Kristallitaggregate aufschmelzen oder aufpressen lassen. Die Kristallite sind als Blättchen ausgebildet, die sich der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1940
1940
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Structural details of the orthorhombic phase have been reported (Bunn, 1939;Hengstenberg, 1928;King and Garner, 1936;Muller, 1928Muller, , 1929aMuller, , 1930Muller and Saville, 1925;Smith, 1932Smith, , 1953Teare, 1959;Vainshtein and Pinsker, 1951;Vand, 1953;Wyckoff, 1960). The .subcell is orthorhombic.…”
Section: Orthorhombicmentioning
confidence: 97%
“…Structural details of the orthorhombic phase have been reported (Bunn, 1939;Hengstenberg, 1928;King and Garner, 1936;Muller, 1928Muller, , 1929aMuller, , 1930Muller and Saville, 1925;Smith, 1932Smith, , 1953Teare, 1959;Vainshtein and Pinsker, 1951;Vand, 1953;Wyckoff, 1960). The .subcell is orthorhombic.…”
Section: Orthorhombicmentioning
confidence: 97%
“…For example, when long-chain paraffins or their binary solid solutions are deposited onto a nucleating substrate from the vapor phase, the resultant solid 38 initially has the same structure seen for PE600. In fact, very long chain paraffins that do not undergo chain folding may form this structure spontaneously, 39 when crystallized from the melt. However, in these examples, annealing gradually improves the layer separation of the average structure, until a true lamellar structure can be reached as an end point, 38 since the chain length distribution is either very narrow or monodisperse, permitting the formation of layers with well-defined end planes.…”
Section: Discussionmentioning
confidence: 99%
“…Later Piper and Grindley (59), Muller (50), Shearer (66), and Muller and Shearer (52), working with soaps and fatty acids, found that a parallel arrangement of chains in which the atoms were arranged in zigzag fashion accounted well for the x-ray results on these compounds. Subsequent work by Muller (51), Hengstenberg (28), and others has established beyond all doubt the essential correctness of this configuration of the hydrocarbon chains in the crystalline aliphatic compounds.…”
Section: Low Molecular Chain Compoundsmentioning
confidence: 96%